Assessment of health risk due to the exposure of heavy metals in soil around mega coal-fired cement factory in Nigeria - Kolo, Matthew Tikpangi; Khandaker, Mayeen Uddin; Amin, Yusoff Mohd; Abdullah, Wan Hasiah; Bradley, David Andrew; Alzimami, Khalid Sulaiman (Elsevier, 2018)
Mobilization and dispersion of potentially toxic elements into the atmosphere and human environment due to industrial and anthropogenic activities have been associated with significant human health challenges. In this investigation, 20 surface soil samples collected around a coal-fired cement factory in northeast Nigeria were analysed for their heavy metal (Cr, Pb, Ni, Cu, Zn and Mn) concentrations using inductively coupled plasma mass spectrometry. The results showed that mean concentrations of heavy metals, except for Cr were lower than their normal backgrounds (Cr = 76.44 > 64 mg kg−1, Pb = 19.32 < 70 mg kg−1, Ni = 29.09 < 50 mg kg−1, Cu = 5.03 < 63 mg kg−1, Zn = 10.15 < 200 mg kg−1) provided in the Canadian soil quality guidelines. Potential health risk assessment for adults and children for lifetime exposure through ingestion, inhalation and dermal contact were estimated. Statistical analysis identified anthropogenic activities as the principal source of metal contamination in the studied soils. Risk assessments indicated that ingestion pathway is the primary exposure route for both adults and children. Children were found to be prone to higher health risk possibly due to their hand-to-mouth dietary habits. Carcinogenic and non-carcinogenic health risk values were within safety limits for all the metals, though Cr showed a high potential for occurrence of non-carcinogenic health effects in the subpopulations.